(untitled) (Research, Society and Development, 2021)
The prevalence of urinary incontinence is greater in women, physically active and high-performance athletes due to the great effort performed during physical training. The aim of this study is to define the role of physical therapy in urinary incontinence in women who practice physical activity, demonstrating how the main physical therapy treatment techniques used to treat this dysfunction that directly or indirectly interferes in the quality of life of those who suffer from this pathology. Methodology: This is a literature review study, a literature review was carried out in the Bireme databases, the Latin American and Caribbean Literature Database in Health Sciences (LILACS), in the Scientific Electronic Library Online databases (SciELO) and Scholar Google (Google Scholar). Results: Physiotherapy is essential in the treatment of urinary incontinence as it promotes body awareness, restores and improves the function of the perineal muscles, in addition to normalizing muscle tone, helping women to regain good urinary continence, thus improving their quality. of life. Conclusion: there are several physiotherapeutic modalities that can help to improve the function of the pelvic outbreak muscles, including electrical stimulation, kinesiotherapy, vaginal cones, biofeedback and behavioral re-education, containing various resources and techniques that can be used to improve health levels pathology and consequently having a positive effect on the quality of life of patients. However, the benefits of this conservative treatment are given not only by a single therapeutic modality, but by the association of different forms and resources of treatment available according to the complaint and symptoms presented and the good adherence and evolution of each woman.